2006
DOI: 10.2337/dc06-0637
|View full text |Cite
|
Sign up to set email alerts
|

Low Testosterone and High C-Reactive Protein Concentrations Predict Low Hematocrit in Type 2 Diabetes

Abstract: OBJECTIVE -After the demonstration that one-third of male patients with type 2 diabetes have hypogonadotrophic hypogonadism, we have shown that patients with hypogonadotrophic hypogonadism also have markedly elevated C-reactive protein (CRP) concentrations. We have now hypothesized that type 2 diabetic subjects with hypogonadotrophic hypogonadism may have a lower hematocrit because testosterone stimulates, whereas chronic inflammation suppresses, erythropoiesis.RESEARCH DESIGN AND METHODS -Seventy patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
86
2
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 26 publications
13
86
2
7
Order By: Relevance
“…This is consistent with the known erythropoietic effect of testosterone. We have previously shown that hemoglobin concentrations are lower in hypogonadal type 2 diabetic men without CKD (30). Our current data indicate that this is true in type 2 diabetic men with CKD as well.…”
Section: Discussionsupporting
confidence: 68%
“…This is consistent with the known erythropoietic effect of testosterone. We have previously shown that hemoglobin concentrations are lower in hypogonadal type 2 diabetic men without CKD (30). Our current data indicate that this is true in type 2 diabetic men with CKD as well.…”
Section: Discussionsupporting
confidence: 68%
“…Testosterone levels remained associated with anemia independent of confounders such as age, renal function, systemic inflammation and iron stores, and determined a remarkable 6%-8% of the total variability in hemoglobin levels. 15 These findings that testosterone deficiency may contribute to an increased frequency of anemia in men with diabetes, confirmed elsewhere, 16 are important not only because of the high prevalence of low testosterone levels in men with diabetes, 17 but also because of the overlapping symptomatology of hypogonadism with anemia. 18 Whether diabetic men presenting with anemia should be screened for testosterone deficiency and vice versa deserves further study.…”
supporting
confidence: 49%
“…While earlier animal and human studies have shown that androgens increase the synthesis and secretion of erythropoietin, 10 a more recent prospective study showed that while testosterone dose-dependently increased hemoglobin and hematocrit levels in chemically castrated men, there was no associated increase in erythropoietin. 23 In addition, in population-based studies of men with 15,16 and without diabetes, 21 low testosterone remained a risk factor for anemia independent of erythropoietin levels. Consistent with the notion that hemopoietic actions of androgens are erythropoietin-independent are findings from studies in men undergoing hemodialysis, which found that concurrent androgen therapy not only augmented the anti-anemic effects of erythropoietin, but also reduced the erythropoietin dose necessary to maintain the target hemoglobin level.…”
Section: Hematological Effects Of Adt M Grossmann and Jd Zajac 188mentioning
confidence: 99%
“…Thus, LH and FSH concentrations in the normal reference range would be considered to be "low" when associated with low serum free testosterone concentrations. 2 While C-reactive protein levels was measured by using a high sensitivity enzyme linked immunosorbant Assay kit. hsCRP levels >3 mg/l were termed "high" because those concentrations are known to be associated with increased cardiovascular events.…”
Section: Lh (Luteinising Hormone) and Fsh (Follicle Stimulating Hormone)mentioning
confidence: 99%
“…Low serum testosterone level is also associated with high c-reactive protein levels which is a marker of ongoing systemic inflammation. 2 The male diabetic patients who have low free serum Testosterone level and high c-reactive protein levels have an association with low hematocrit and a frequent occurrence of mild normochromic normocytic anemia. Testosterone is known to stimulate the proliferation of erythroid progenitors, largely by erythropoietinindependent mechanisms.…”
Section: Introductionmentioning
confidence: 99%